Effect of Structural Modifications on the Self‐Assembly of Oligoprolines Conjugated with Sterically Demanding Chromophores. Issue 11 (17th February 2016) - Lewandowska, Urszula; Zajaczkowski, Wojciech; Pisula, Wojciech; Ma, Yingjie; Li, Chen; Müllen, Klaus; Wennemers, Helma
Abstract: Conjugates between oligoprolines and sterically demanding perylene monoimides (PMIs) form hierarchical supramolecular self‐assemblies. The influence of the length and stereochemistry at the attachment site between the peptide backbone and the chromophore on the self‐assembly properties of the conjugates was explored. Comparison between oligoprolines bearing 4 R ‐ or 4 S ‐configured azidoprolines (Azp) for the conjugation with the PMIs revealed that diastereoisomers with 4 R configuration guide the self‐assembly consistently better than conjugates with 4 S configuration. Elongating the peptide chain beyond nine proline residues or introducing structural "errors", by altering the absolute configuration of one stereogenic center at the outside of the functionalizable oligoproline helix, lowered the efficacy of self‐assembly significantly, both in solution phase and in the solid state. The results showed how subtle structural modifications allow for tuning the self‐assembly of chromophores and provided further design principles for the development of peptide–chromophore conjugates into nanostructured materials. Abstract : Length and orientation matters : The length and stereochemistry of conjugates between oligoprolines and sterically demanding perylene monoimides can be used to tune their supramolecular assembly properties (see figure). Structural errors are tolerated in the best performing conjugates.